Unleashing Competitive Edge: Empowering the IT Sector with CSR Excellence - Sayedeh Parastoo, Saeidi (2023)
While numerous scholars have concentrated on investigating the repercussions of Corporate Social Responsibility (CSR) on diverse aspects of business across various industries, there persists a research void in conducting comprehensive analyses of CSR tactics within the Information Technology (IT) sector. Therefore, this study seeks to bridge this gap by appraising the repercussions of CSR on competitive advantage within IT firms. The outcomes from a sample of 98 Malaysian IT enterprises reveal that, among the four CSR components — legal, ethical, economic, and discretionary — the legal, ethical, discretionary, and economic dimensions positively influence competitive advantage in descending order. These collective findings indicate a noteworthy function of CSR in amplifying competitive advantage within IT companies in Malaysia.